Hubungan Persepsi Keluarga Tentang Gangguan Jiwa Dengan Dukungan Keluarga Dalam Pemulihan Orang Dengan Gangguan Jiwa (ODGJ) Di Wilayah Kerja Puskesmas Pajangan - Mentang, Nadya Novita; Azizah, Fajriyati Nur (Jurnal Riset Daerah, 2021)
Mental disorder is a behavioral syndrome which is clinically related to the distress of suffering. It may also result disorders in one or more functions of human life. Perception is a process of observing the outside world covering attention, understanding, and introduction of objects or events. An individual diagnosed of having mental disorder needs more attention and support from the surroundings particularly from their family. This research aims to find out the correlation of family perception on mental disorder and family support in the recovery of people with mental disorder (ODGJ). This research applied descriptive corellative with cross sectional design using simple random sampling technique to 51 respondents. The research instrument used the family perception questionnaire (Nugroho, 2016) and family support questionnaire (Nurwulan, 2017). The research result were analyzed using the spearman rank formula. The value was p=0.350 (>0.50). the research results show that most respondents have perception categorized as good (90.1%). Meanwhile, the results of family support is that most respondens have fair support (68.7%.). There is no correlation between family perception on mental disorder and family support in the recovery of people with mental disorders (ODGJ) in the working area of Puskesmas Pajangan Bantul. Its expected that the next researchers are able to deveop this research using other methods such as qualitative so that deeper information on perception and family support toward the people with mental disorder (ODGJ).